Surface strain at the cervical area and fracture strength of flared root canals reinforced using a zirconia tube and glass-fiber post - Daiki Kondo; Wataru Komada; Shinya Oishi; Kenji Fueki (Elsevier, 2024)
Background/purpose: Recently, an effective core build-up system for teeth with flared root canals is needed. This research aimed to evaluate the effect of foundation restorations using a composite resin core with a fiber post reinforced with a zirconia tube for the surface strain at the cervical area and the fracture load of teeth with flared root canals. Materials and methods: Bovine teeth were shaped to mimic human premolars with flared root canals and restored using three types of composite resin foundation restorations with each materials described below: a fiber post (FC), a zirconia tube (ZC), a fiber post and zirconia tube (ZFC). Each specimen was restored with a zirconia crown. The surface strains of the specimens at the cervical area and fracture loads were analyzed using a one-way analysis of variance (ANOVA), followed by Tukey's honest significant difference test. Results: The surface strains of Groups ZFC and ZC were significantly lower than that of Group FC in the buccal root. The fracture strengths of Groups ZFC and ZC were significantly higher than that of Group FC. The strength of Group ZFC was significantly higher than that of Group ZC. Conclusion: The use of a composite resin core with a zirconia tube for the simulated premolar with flared root canals reduced surface strain at the cervical area and provided higher fracture strength compared to using a composite resin core with a fiber post. And the zirconia tubes provided even higher fracture strength when used with a fiber post.